The Effect of Active and Passive Cooling Down Exercises on Reducing The Pulse Heart Rate of Female Volleyball Athletes - Syari’ah, Kanaya Siti Nur; Pitriani, Pipit; Novian, Geraldi (Journal of Sport Science and Fitness, 2025)
Introduction: A decrease in pulse rate is the most important part that can be measured to support the effectiveness of the training program. In volleyball, which requires a long game time, coaches must also know the process of effective and efficient cooling exercises that can be used to lower the pulse rate. Cool-down training is one way to reduce the pulse rate. Objectives: This study aims to measure the effects of active and passive cooling exercises on physiological responses, one of which is pulse rate. Method: The method used in this study is a quantitative method with an experimental approach with a research design of a two-group pre-test post-test design. The population in this study was Female Volleyball Athletes of Club Bahana Bina Pakuan Bandung City, with an age group of 15-17 years, many of 16 people. The sampling technique used was total sampling, with a total population of 16 people who became the research sample. The instrument used is a Polar H10 device to measure the pulse rate that drops when given active and passive cooling exercises. Result: The results of this study indicate that a more significant decrease in pulse rate is achieved when using active cooling exercises; the effectiveness obtained is 5.70%, whereas passive cooling exercises result in a significant decrease by 3.68%. Conclusion: This study provides recommendations for coaches to continue to see the decline that occurs when given a cooling exercise program. It is also expected that coaches have polar devices to monitor the condition of athletes.